2015
DOI: 10.1126/scisignal.2005916
|View full text |Cite
|
Sign up to set email alerts
|

Heparin is an activating ligand of the orphan receptor tyrosine kinase ALK

Abstract: Anaplastic lymphoma kinase (ALK) is one of the few remaining "orphan" receptor tyrosine kinases (RTKs) in which the ligands are unknown. Ligand-mediated activation of RTKs is important throughout development. ALK is particularly relevant to the development of the nervous system. Increased activation of RTKs by mutation, genetic amplification, or signals from the stroma contributes to disease progression and acquired drug resistance in cancer. Aberrant activation of ALK occurs in subsets of lung adenocarcinoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 21 publications
3
58
0
Order By: Relevance
“…We have previously shown that heparin binds to the NTR region of ALK and stimulates the receptor's kinase activity in NB1 cells (15). Therefore, we studied the effect of heparin on ALK in the presence and absence of AUG-α.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that heparin binds to the NTR region of ALK and stimulates the receptor's kinase activity in NB1 cells (15). Therefore, we studied the effect of heparin on ALK in the presence and absence of AUG-α.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we have shown that heparin can bind to the NTR domain of ALK and can activate ALK expressed in NB1 cells (15). However, the role of the two MAM and LDL-A domains remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies published earlier this year, Murray et al, also in the Schlessinger group, identified heparin as an activating ligand for ALK in NB-1 neuroblastoma cells (14). These investigators found that acidic sulfated glycosaminoglycan polymers bound to the very basic amino terminus of ALK, and strongly potentiated ALK autophosphorylation in NB-1 cells.…”
mentioning
confidence: 89%